Restricted Agreements for Competition Between Prohibition and Justification - Lahouaoula, Amel (Journal of Human Sciences, 2023)
The freedom of competition means the freedom of traders, wither Natural or legal persons, to enter the commercial market, to practice various commercial transactions and to seek goods and services in which the best prices and specifications are available. The freedom of competition, without controls may lead to monopoly. This is the most dangerous practice restricting freedom of competition. This is the main reason for the legislator’s intervention in the development of legislation and regulation what join this competition and ensure its protection and prevent the occurrence of monopoly. The agreements that are considered among the restrictive practices of the competitions and the legislator cause to the attention of the agreements means to attend all forms of alliance and collusion between institutions as these actions effect the most unimportant conditions love in the institutions, which is the independence of decision marketing, although the agreement is in its own accord.